Pengaruh Penggunaan Simulasi PhET dalam E-Modul terhadap Hasil Belajar Siswa pada Materi Listrik Magnet - Faradisa Khairunnastuti; Ismet; Wiyono Ketang (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to determine the effect of using PhET (Physics Education Technology) simulations on e-modules covering electric and magnetic materials on the learning outcomes of students at SMA N 2 Muhammadiyah in the 2023/2024 academic year. The type of research used is a descriptive method with a quantitative approach. The population of this study is all students in grade XII of SMA N 2 Muhammadiyah, with a total of 90 participants. The sampling technique used was cluster random sampling, and grade XII was selected as the class to be tested. Grade XII was taught using the direct learning model with the PhET (Physics Education Technology) simulation media. After obtaining the final test results for the class, which were homogeneous and normally distributed, the research hypothesis was tested using a paired-sample test with a significance level of 5% and obtained a Sig. (2-tailed) value of 0.000, so it can be said that the Sig. value is < 0.05. Based on the results, it can be concluded that there is an effect of using PhET (Physics Education Technology) simulation media on students' physics learning outcomes.